Distribution Patterns of Floating Microplastics in Open and Coastal Waters of the Eastern Mediterranean Sea (Ionian, Aegean, and Levantine Seas) - Adamopoulou, Argyro; Zeri, Christina; Garaventa, Francesca; Gambardella, Chiara; Ioakeimidis, Christos; Pitta, Elli (Frontiers in Marine Science, 2021)
Microplastic pollution is a pervasive anthropogenic phenomenon at the ocean surface. Numerous studies have been performed worldwide; nevertheless, the distribution patterns, morphological properties and sources of origin in the Eastern Mediterranean Sea are still poorly explored. The purpose of this study is to investigate the distribution patterns of surface floating microplastics (MPs) in the Ionian, Aegean and Levantine Seas in relation to their sources and sea surface circulation. In total, eighty-four (84) samples were collected using manta nets from 2014 to 2020, covering open waters, coastal waters and enclosed gulfs (Corfu and Saronikos). MPs concentration measurements revealed high variability ranging from 0.012 to 1.62 items m-2 and did not present maximum concentrations close to MPs hotspot areas. The presence of sea surface slicks, as recorded visually during our samplings, seems to play a key role on the distribution pattern of MPs, and highest concentrations were recorded in samples affected by these formations. The dominant MPs shape type identified were fragments (50% - 60%), whilst filaments (1% - 23%), films (3% - 26%) and foams (0% - 34%) varied among the studied areas. The majority of MPs in open waters had sizes ≤ 2 mm peaking between 0.6 mm and 1.4 mm. Spectroscopic analysis of MPs revealed the presence of eleven (11) polymer types in both open sea and gulfs; the most abundant type was polyethylene (PE), followed by polypropylene (PP) and polystyrene (PS). The relative abundance of polymer types was more diverse in Saronikos Gulf, compared to the open sea due to the proximity to major urban and industrial sources. Our findings suggest that the vicinity to coastal population centers determined the properties, size and polymer types of MPs and highlight that MPs concentrations are affected significantly by local oceanographic conditions, such as surface slicks.